When I grew up long ago : family living, going to school, games and parties, cures and death, a comet, a war, falling in love, and other things I remember : older people talk about the days when they were young - Schwartz, Alvin; Berson, Harold (Lippincott, 1978)
Brief statements from people whose childhoods were in the period 1890-1914 on such areas of their past lives as food, social life, music, holidays, and health present glimpses of life in the United States at that time.